2016
DOI: 10.1007/978-3-319-25474-6_25
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Contributions of Temporal Envelope and Fine Structure to Mandarin Lexical Tone Perception in Auditory Neuropathy Spectrum Disorder

Abstract: Previous studies have demonstrated that temporal envelope (E) is sufficient for speech perception, while fine structure (FS) is important for pitch perception for normal-hearing (NH) listeners. Listeners with sensorineural hearing loss (SNHL) have an impaired ability to use FS in lexical tone perception due to the reduced frequency resolution. Listeners with auditory neuropathy spectrum disorder (ANSD) may have deficits in temporal resolution. Little is known about how such deficits may impact their ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Temporal information refers to information in speech signals with time-varying wave rates, which can be divided into the temporal envelope (E) below 50 Hz, periodic fluctuations in the range of 50-500 Hz, and temporal fine structure in the range of 500-10,000 Hz (Rosen, 1992). E cues contain temporal modulation information, which is most important for speech perception in quiet conditions, whereas the temporal fine structure can provide information in noisy environments and for tonal and pitch recognition (Smith et al, 2002;Xu and Pfingst, 2003;Moore, 2008;Ardoint and Lorenzi, 2010;Wang et al, 2016). Vocoder studies have shown that E modulation rates of 4-16 Hz are most important for speech intelligibility in quiet (Drullman et al, 1994a,b;Shannon et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Temporal information refers to information in speech signals with time-varying wave rates, which can be divided into the temporal envelope (E) below 50 Hz, periodic fluctuations in the range of 50-500 Hz, and temporal fine structure in the range of 500-10,000 Hz (Rosen, 1992). E cues contain temporal modulation information, which is most important for speech perception in quiet conditions, whereas the temporal fine structure can provide information in noisy environments and for tonal and pitch recognition (Smith et al, 2002;Xu and Pfingst, 2003;Moore, 2008;Ardoint and Lorenzi, 2010;Wang et al, 2016). Vocoder studies have shown that E modulation rates of 4-16 Hz are most important for speech intelligibility in quiet (Drullman et al, 1994a,b;Shannon et al, 1995).…”
Section: Introductionmentioning
confidence: 99%